The Factors Influencing Online Food Delivery Usage Intention on Semi-Endemic Period - Istijanto; Albirra , Fionabella; Soesapto , Michael Joshua; Agata, Luisa; Pribadi, Adinda Marisskeputri; Lydia Apriliani (Universitas Airlangga, 2023)
Background: In 2021, food delivery apps users in Indonesia reached the world highest number amounting 74.4% users. The main reason is the implementation of COVID-19 health protocol in Indonesia which limits outdoor activities. However, the COVID-19 pandemic situation in Indonesia indicates that COVID-19 is in the final phase of moving towards endemic or can be called a Semi-endemic phase since Indonesia government regulations, regarding COVID-19 health protocol, are getting loose by allowing people to do outdoor activities. Objective: This study aims to examine the relationship between the variables in Theory of Planned Behavior (TPB), which consists of; attitude, subjective norms, perceived behavioral control and trust, and perceived risk in predicting online food delivery behavioral intention during the Semi-endemic period in Indonesia. Method: This study adopts a quantitative research which employs 303 respondents who filled out an online questionnaire about food delivery applications usage for three months starting in July 2022. Results: Attitude, perceived behavioral control, and trust are positively and directly influencing the usage intention, while subjective norms do not. There were two risk variables, namely privacy risk and COVID-19 risk, which had a significant impact on consumers' online food delivery usage intention. Conclusion: Based on TPB, trust, and risk, this study showed that attitude, perceived behavioral control, trust, COVID-19 risk and privacy risk are significant in influencing online food application usage intentions in Indonesia during the semi-endemic period. Keywords: online food delivery; online food delivery usage intention; perceived risk; semi endemic; theory of planned behavior.